2022
DOI: 10.3390/min12040434
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Quantitative Assessment of Mineral Resource Potential in the Da Hinggan Mountains in Inner Mongolia, China

Abstract: Studying surface geochemical anomalies is important for detecting the presence of mineral deposits. However, distinguishing inconspicuous geochemical anomalies is a challenge for geochemists. This paper studies geochemical quantitative prediction for Pb–Zn metallic mineral deposits by identifying inconspicuous surface geochemical anomalies mainly associated with the Permian and Jurassic strata in the middle-southern Da Hinggan Mountains metallogenic belt. Some new methods are employed to highlight weak surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The Greater Xing'an Range (GXAR) metallogenic belt is located in Central Asian Orogenic Belt (Figure 1A), which is one of the nineteen important metallogenic belts in China (Yang, 2017). Metallogenic elements such as Sn, Fe, Pb, Zn, Au, Cu, Ag, and Mo are associated with or zoned (Zhang et al, 2013;Liu et al, 2016;Zhou et al, 2019).…”
Section: Geological Setting and Exploration Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The Greater Xing'an Range (GXAR) metallogenic belt is located in Central Asian Orogenic Belt (Figure 1A), which is one of the nineteen important metallogenic belts in China (Yang, 2017). Metallogenic elements such as Sn, Fe, Pb, Zn, Au, Cu, Ag, and Mo are associated with or zoned (Zhang et al, 2013;Liu et al, 2016;Zhou et al, 2019).…”
Section: Geological Setting and Exploration Criteriamentioning
confidence: 99%
“…According to the existing reports, the Weilasituo-bairendaba district is an important component of the Cu-Pb-Zn metallogenic belt (Yang, 2017;Zhang, 2017). The known Weilasituo Cu-Zn deposit and Bairendaba Ag-Pb-Zn deposit have many similarities in stratigraphy, intrusions, structure, geophysics, and geochemistry (Tang et al, 2014;Zhang, 2017;IMGECL, 2018).…”
Section: Frontiers In Earth Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Chun et al (2021) using a semi-variance-based model showed that the heavy metals content gradually decreased with increasing distance from the tailings pond in the Baiyinhua mining area of Inner Mongolia Autonomous Region, China. Yang et al (2022) found that soil pH, organic matter, and cation exchange are important factors driving the transformation of soil heavy metals forms.…”
Section: Introductionmentioning
confidence: 99%
“…Inner Mongolia has huge mineral reserves, which is of great significance to the arrangement of mineral resources in China (Yang et al, 2022). Due to the fact that most of the mineral resources in Inner Mongolia are located in grasslands ecosystem with a weak resistance to disturbance, mining activities can lead to a great threat to the ecosystem.…”
Section: Introductionmentioning
confidence: 99%